The Role of Informed Consent in Medical Disputes at State University Hospitals - Putu Agus Prawira Eka Putra; I Gusti Ayu Putri Kartika; R.A. Tuty Kuswardhani (Unram Law Review, 2024)
The research aims to understand how informed consent functions in the context of medical disputes at state university hospitals in Indonesia. The main benefit of the study is to provide an overview of how informed consent offers legal protection to the medical profession, particularly in resolving disputes that may arise in the hospital setting. The research utilizes a normative legal research method, focusing on the examination of written laws, regulations, and legal materials applicable in Indonesia. The research concludes that the thoroughness of informed consent documentation is crucial, especially for medical procedures that carry high risks. This thoroughness serves as a legal safeguard for medical professionals, ensuring their protection in case of disputes. Enhanced attention to the completeness of informed consent is necessary to mitigate the risks for doctors and provide legal security within the medical field at state university hospitals.